245 Arrhythmogenic cardiomyopathy in children according to 'padua criteria': single paediatric centre experience. (8th December 2021) - Cicenia, Marianna; Cantarutti, Nicoletta; Adorisio, Rachele; Silvetti, Massimo Stefano; Secinaro, Aurelio; Ciancarella, Paolo; Di Mambro, Corrado; Magliozzi, Monia; Novelli, Antonio; Amodeo, Antonio; Baban, Anwar; Drago, Fabrizio
Abstract: Aims: Arrhythmogenic cardiomyopathy (ACM) is a rare disease in children. The purpose of this study is to describe the main features of our paediatric patients with ACM providing a contribution for diagnostic work-up and therapeutic decisions. Methods and results: Eligibility criteria of the study was ACM diagnosed at age <18 years old. We enrolled 21 patients (mean age at diagnosis 13.9 ± 2 years). Holter monitoring showed premature ventricular complexes (PVCs) burden of 7.9 ± 10% (range: 1–35%). Exercise testing showed suppression of PVCs during exercise in most patients (44.4%). Cardiac magnetic resonance was performed in 17/21 (81%) patients. Right ventricular (RV) dilatation, segmental wall motion abnormalities, and late gadolinium enhancement of both ventricles were the predominant features. Genetic results were available in 19/21 patients. 3/19 (15.8%) had compound heterozygous variants, 3/19 (15.8%) digenic variants, and 6/19 (31.6%) a single variant. EPS was performed in 15/21 (75%). Ventricular tachycardia was inducible in 3/15 (20%) and ventricular fibrillation occurred in 1/15 (6.7%). Implantable cardiac defibrillators (ICDs) were implanted in 15 patients (71.4%). ICD therapies were released in two patients during follow-up (2009–2021). No patients died suddenly. Conclusions: Paediatric ACM can be diagnosed in the majority of cases secondary to: incidental finding of minor arrhythmias or due to positive family history. PVCs burden is not elevated and exercise-induced arrhythmias occur in a minority of patients. ICD may be indicated in most patients even if follow-up during the paediatric age can be reassuring. Multicentric observation is highly needed to derive conclusions in children.